PEMANFAATAN BAHAN ALAMI BIOAKTIF TANAMAN (BABT) DALAM PRODUKSI TOMAT CHERRY ORGANIK - Sjam, Sylvia; Syam'un, Elkawakib; Sartika Dewi, Vien (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2020)
Cherry tomatoes have an economic advantage compared to other tomatoes, namely their high and stable selling price. Organic cherry tomato production without synthetic chemical residues is one of the farming activities that can be carried out or managed to increase income sources. The biggest problem in almost all vegetable crop centers that grow tomatoes in South Sulawesi is the high application of synthetic chemical compounds including synthetic fertilizers and pesticides. At the center, no one has produced organic tomatoes even though the demand is high, so the cherry tomatoes are imported from outside South Sulawesi. The above phenomenon shows that there is a need for efforts to develop and plant organic cherry tomatoes through a business unit. This opportunity is very good because the market, especially supermarkets in South Sulawesi, is still lacking in organic cherry tomatoes and tomatoes are also needed in restaurants. The long-term goal is to create a technology-based business unit that comes from several studies. The technological innovation that will be applied is an organic cultivation system, which is environmentally friendly technology starting from a seed treatment with formulations that have been obtained from natural ingredients, the use of microorganisms and natural bioactive plant materials for the manufacture of organic fertilizers (solid and liquid fertilizers), and controlling pests and diseases (plant pests) with extracts of natural bioactive plant materials (NBPM). Trying to make an effort to produce organic cherry tomatoes more commercially so that it is expected to be a profitable entrepreneur. Activities start from the selection of raw materials, the planting process to the production process using environmentally friendly technologies without synthetic chemical intake in accordance with SNI standards using a planting schedule for sustainable production. ABSTRAK Tomat cherry memiliki keunggulan ekonomis dibandingkan dengan tomat lain, yaitu harga jualnya yang tinggi dan stabil. Produksi tomat cherry organik tanpa residu kimia sintetik merupakan salah satu aktivitas usaha tani yang dapat dilakukan atau dikelola untuk meningkatkan sumber pendapatan. Masalah yang terbesar pada hampir semua sentra-sentra tanaman sayuran yang menanam tomat yang ada di Sulawesi Selatan adalah tingginya aplikasi senyawa kimia sintetik termasuk pupuk dan pestisida sintetik. Pada sentra tersebut juga belum ada yang meproduksi tomat organik padahal permintaan tinggi sehingga tomat cherry didatangkan dari luar Sulawesi Selatan. Fenomena di atas menunjukkan bahwa perlunya upaya pengembangan dan penanaman tomat cherry organik melalui suatu unit usaha. Peluang ini sangat baik karena dipasaran terutama disupermarket yang ada di Sulawesi Selatan masih sangat kurang tomat cherry organik dan juga tomat ini dibutuhkan di restoran-restoran.Tujuan jangka panjang adalah untuk menciptakan unit usaha berbasis pada tehnologi yang berasal dari beberapa penelitian. Inovasi teknologi yang akan diterapkan adalah sistem budidaya secara organik adalah tehnologi ramah lingkungan mulai dari perlakuan benih (seed treatmen) dengan formulasi yang telah didapatkan yang berasal dari bahan alami, pemanfaatan mikroorganisme dan bahan alami bioaktif tanaman untuk pembuatan pupuk organik (pupuk padat dan cair), dan pengendalian hama dan penyakit (organisme pengganggu tanaman) dengan ekstrak bahan alami bioaktif tanaman (BABT). Produksi tomat cherry organik diusahakan lebih komersil sehingga diharapkan sebagai wirausaha yang bemanfaat. Kegiatan dimulai dari pemilihan bahan baku, proses penanaman sampai proses produksi dengan menggunakan tehnoloi ramah lingkungan tanpa asupan kimia sintetik sesuai dengan standar SNI dengan menggunakan jadwal tanam untuk kesinambungan produksi.